ANALISIS KEBUTUHAN LEMBAR KERJA MAHASISWA (LKM) BERBASIS GREEN CHEMISTRY PADA MATERI TITRASI KONDUKTOMETRI - Edita Putri, Chindy; Sanjaya, Sanjaya (Penerbit Lafadz Jaya, 2026)
Laboratory practicum plays crucial role in chemistry education, yet current materials for conductometric titration lack green chemistry integration, hindering sustainable learning. This study aimed to analyze needs for developing Student Worksheet (LKM) based on green chemistry for conductometric titration in Physical Chemistry Practicum 2. Using descriptive method with qualitative-quantitative approach, population comprised Chemistry Education students at Sriwijaya University who completed the course, with purposive sample of 45 students, 1 lecturer, and 1 lab technician. Instruments included 12-item needs analysis questionnaire and semi-structured interviews, analyzed via descriptive percentages and qualitative thematic reduction. Results showed high student enthusiasm (95.6-97.7%) but low concept understanding (51.1% unclear, 60% found modules difficult), with 68.9% reporting no green chemistry integration despite 84.1% awareness and 100% agreement on its importance. Notably, 95.6% supported LKM development. In conclusion, green chemistry-based LKM is urgently needed to bridge knowledge-practice gaps and enhance sustainable practicum learning.